Editorial - Lourenço, Érika; Assis, Raquel Martins de (Memorandum: Memória e História em Psicologia, 2019)
Editorial 36
Keywords: editorial

Helena Antipoff: Science as a Passport for a Woman’s Career between Europe and Latin America - Campos, Regina Helena de Freitas; Lourenço, Érika (Transversal: International Journal for the Historiography of Science, 2019)
Helena Antipoff was one of the pioneers in the constitution of the fields of knowledge of educational psychology and special education in Brazil. Born in Russia, Antipoff received her education in Paris and Geneva. Researches in the history of education and of psychology have revealed the innovative character of Antipoff’s work as a researcher, as a professor and as a founder of different educational institutions in Brazil, with a focus on educational and psychological care for children with disabilities or at social risk. Her career is characterized by a sound scientific approach combined with a deep commitment to the right of children and youth to education and care. These directions can be associated with her scientific training in the sciences of education in a time of social turbulence and school reform, when many women became professionals in the field of education, trying to combine family, work and militant activity.
Keywords: Educational Psychology; Helena Antipoff; History of Psychology; Psychology of the Exceptional; Special Education; Women in Science; Women in the Sciences of Education